2017
DOI: 10.1111/jdv.14406
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with the choice of the first biologic in psoriasis: real‐life analysis from the Psobioteq cohort

Abstract: We identified patient- and disease-related factors that have important influence on the choice of the first biological agent in clinical practice. Clinicians appear to have a holistic approach to patient characteristics when choosing a biological agent in psoriasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 15 publications
1
21
1
3
Order By: Relevance
“…Variability in treatment efficacy of adalimumab has been observed among these controlled and real-life studies, and causal factors have already been identified. 22,[28][29][30][31][32] While no difference was observed in terms of PASI response between biologic na€ ıve, previous anti-TNF-alpha or previous ustekinumab treatment on the effect of adalimumab, stepwise logistic regression in our study revealed that younger patients, no diabetes/metabolic syndrome, no dyslipidemia, no hypertension or a lower PASI at baseline were significantly associated with better achievement of PASI response by 3 and 6 months. Interestingly, at later time points (1, 2 and 3 years), absence of hypertension and a positive diagnosis for psoriasis/psoriatic arthritis were significantly associated with increased odds of achieving PASI 90 and complete remission (PASI 100).…”
Section: Discussioncontrasting
confidence: 63%
“…Variability in treatment efficacy of adalimumab has been observed among these controlled and real-life studies, and causal factors have already been identified. 22,[28][29][30][31][32] While no difference was observed in terms of PASI response between biologic na€ ıve, previous anti-TNF-alpha or previous ustekinumab treatment on the effect of adalimumab, stepwise logistic regression in our study revealed that younger patients, no diabetes/metabolic syndrome, no dyslipidemia, no hypertension or a lower PASI at baseline were significantly associated with better achievement of PASI response by 3 and 6 months. Interestingly, at later time points (1, 2 and 3 years), absence of hypertension and a positive diagnosis for psoriasis/psoriatic arthritis were significantly associated with increased odds of achieving PASI 90 and complete remission (PASI 100).…”
Section: Discussioncontrasting
confidence: 63%
“…Moreover, in concordance with previous studies in adult psoriasis, adalimumab was received more frequently in patients with severe psoriasis than were etanercept or ustekinumab. 25 No association was found between psoriatic arthritis and the choice of biological therapy. The most commonly prescribed biological agent in our study was etanercept, whereas Sbidian et al 25 reported that adalimumab was the most commonly prescribed agent in adult psoriasis.…”
Section: Discussionmentioning
confidence: 99%
“…25 No association was found between psoriatic arthritis and the choice of biological therapy. The most commonly prescribed biological agent in our study was etanercept, whereas Sbidian et al 25 reported that adalimumab was the most commonly prescribed agent in adult psoriasis. This difference between the two studies can be explained by the fact that etanercept was the first biological agent to be approved in children in 2008.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations